Analisis Kualitas Layanan IndiHome Menggunakan Metode SERVQUAL dan Improvement Gap Analysis (IGA) - Theresia Pawitra; Yunika Rinda Suryana; Dharma Widada (Jurnal Industri Samudra, 2026)
Indihome (Indonesia Digital Home) is a service product that provides internet, television, and telephone services. As an internet service provider, IndiHome is expected to ensure that its customers receive the best possible service experience. In this study, the researcher analyzed the service quality delivered by IndiHome using the Servqual method to measure service quality and the Improvement Gap Analysis (IGA) method to identify priority attributes that require improvement. The results of the Servqual analysis showed that 15 service attributes had negative gaps, while 7 attributes had positive gaps. These attributes were then further analyzed using the IGA method, which classified them into four quadrants: 7 attributes were categorized in Quadrant I, 4 attributes in Quadrant II, 8 attributes in Quadrant III, and 3 attributes in Quadrant IV. A Z-Test was subsequently conducted to determine the significance of the gaps between customer perceptions and expectations. The results revealed that three attributes had significant gaps. These included the attribute stating that employees provide clear information regarding the certainty of service execution time, which was classified in Quadrant IV, as well as the attributes stating that IndiHome employees are always willing to help customers and consistently behave politely, both of which were classified in Quadrant I. Since all three attributes showed negative gaps, improvement recommendations were considered necessary. To formulate these recommendations, an analysis of the causes of Gap 5 was carried out by examining the contributing causes of Gap 1, Gap 2, Gap 3, and Gap 4.